Poder y representaciones: elementos para la construcción del campo político en la teoría de Bourdieu. - B. Gutiérrez, Alicia (Revista Complutense de Educación, 2006)
The "properly politic game", the politic field, in the perspective of Pierre Bourdieu is a field as any other field, that is to say, it is submitted to the same general laws described for all the fields in general, although these same laws get their own properties in the space of the concrete game. In order to explain these properties, within the general frame of the theory of the fields, it is necessary to refer to other central aspects in the perspective of Pierre Bourdieu, in the frame of which they can be understood. That is why in this paper, we make reference to the notion of "symbolical power" in the first place, next we refer to the representations and their role in the symbolical fights; afterwards we point out the specific characteristics in the political field and finally we emphasize the role of the intellectuals within the frame of this analytic conception.